2015
DOI: 10.1038/srep15378
|View full text |Cite
|
Sign up to set email alerts
|

From Crystals to Disordered Crystals: A Hidden Order-Disorder Transition

Abstract: To distinguish between order and disorder is of fundamental importance to understanding solids. It becomes more significant with recent observations that solids with high structural order can behave like disordered solids, while properties of disordered solids can approach crystals under certain circumstance. It is then imperative to understand when and how disorder takes effect to deviate the properties of a solid from crystals and what the correct factors are to control the behaviours of solids. Here we answ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 58 publications
7
94
0
Order By: Relevance
“…Because relating microscopic features with macroscopic rheology is still unsolved, it is unclear whether our findings relate with those of the universality class proposed in Ref. 19, but this hypothesis deserves further consideration. The specific exponent values and their violation of the stability bounds for marginal solids observed in these systems should also motivate additional study.…”
mentioning
confidence: 77%
“…Because relating microscopic features with macroscopic rheology is still unsolved, it is unclear whether our findings relate with those of the universality class proposed in Ref. 19, but this hypothesis deserves further consideration. The specific exponent values and their violation of the stability bounds for marginal solids observed in these systems should also motivate additional study.…”
mentioning
confidence: 77%
“…Atoms are identical, but colloids inevitably have a polydispersity that is typically >3%. A polydispersed system can self‐assemble into not only a less ordered structure, but also qualitatively different crystals . Polydispersity shifts the melting point, hexatic regime and coexistence regime in both 2D and 3D .…”
Section: Other Factors Affecting Meltingmentioning
confidence: 99%
“…These two peaks apparently develop from the van Hove singularities and always stay at roughly the same frequencies. It has been shown that the emergence of the boson peak in this case is a signature of the transition from crystals to disordered crystals, i.e., solids with fairly high crystalline order but sufficiently strong local coordination number fluctuation and the mechanical and vibrational properties of disordered solids [35]. creasing η b , the Ioffe-Regel frequencies decrease and approach ω BP .…”
Section: Local Coordination Number Disordermentioning
confidence: 99%